Implementation of convective heating in Companhia Siderúrgica Nacional Blast Furnace runners - Vidal de Almeida, Bruno; Silva, Sidiney Nascimento; Lopes, José Milton G.; Passos, Ricardo Leite; Longo, Elson [UNESP]; Vernilli, Fernando (Elsevier, 2013)
This paper describes the main characteristics and advantages of convective heating system for refractory lining, compared with conventional heating systems. In addition the main results obtained are presented with its implementation in CSN Blast Furnace #2 and 3 Runners, in terms of cost and equipment availability, as well as the need for ceramic coating to protect the lining against oxidation, arising from excessive air combustion. © 2012 Elsevier Ltd. All rights reserved.
Keywords: Blast Furnace; Convective heating; Runners; Air combustion; Conventional heating; Refractory lining; Ceramic coatings; Heating equipment; Blast furnaces